Occurrence Et Evaluation Du Risque De L’histamine Dans Les Produits De La Peche Commercialises Sur Le Marche Marocain - El Hariri, Oleya; Bouchriti, Noureddine; Bengueddour, Rachid (European Scientific Journal, ESJ, 2017)
The histamine levels of preserved and semi-preserved fish marketed in Morocco from 2013 to 2015 have been determined. This study presents the results of histamine control plan of 446 samples of fishery products collected from different areas of Morocco: retail markets, supermarkets, commercial and social restaurants. The synthesis of the data revealed that the occurrence of histamine is low with a non-compliance rate of 3.14 %. This rate is 2.02 % for canned sardines and 1.12 % for semi-preserved anchovies. The average histamine values of all batches analyzed did not exceed 5.63mg/100g. Average values were 5.14 mg/100 g for canned sardine and 7.76 mg/100 g for semi-preserved anchovies. These levels are much lower than the regulatory safety limit. Two qualitative risk assessments of histamine were carried out, one according to the marketing region and the other with reference to the places of marketing. The results showed that the area with the lowest risk is the northern coastal zone with an average of 2.11 mg/100 g and a non-compliance rate of 0.22%. Low-risk marketing places are the social type restaurants with an average of 4.14 mg/100g and a noncompliance rate of 0.22%. A ranking of various cities in Morocco was carried out according to histamine content of the marketed fishery products. The results demonstrate the relevance of the official control plan established by the competent Moroccan authority and the control measures implemented by the professionals. It can therefore be concluded that preserved and semipreserved fish marketed in Morocco are safe as related to the risk of histamine.